2003
DOI: 10.1002/art.11253
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid neutrophils transcribe and express class II major histocompatibility complex molecules in rheumatoid arthritis

Abstract: Objective. To investigate a potential interaction between neutrophils and T cells in rheumatoid arthritis (RA), by defining the optimal conditions for induction of class II major histocompatibility complex (MHC) expression on peripheral blood neutrophils in vitro and investigating the capacity for neutrophils to express class II MHC molecules in RA.Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 75 publications
3
87
1
11
Order By: Relevance
“…Because class II MHC is required for antigen presentation and T cell stimulation, enhanced expression of class II MHC would lead to enhanced T cell activation and subsequent cellactivation events in the joints of mice that received circulating fibrocytes. Notably, neutrophils derived from the synovial fluid of patients with RA express class II MHC (39).…”
Section: Discussionmentioning
confidence: 99%
“…Because class II MHC is required for antigen presentation and T cell stimulation, enhanced expression of class II MHC would lead to enhanced T cell activation and subsequent cellactivation events in the joints of mice that received circulating fibrocytes. Notably, neutrophils derived from the synovial fluid of patients with RA express class II MHC (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although still expressing the usual neutrophil cell surface markers CD32, CD18 and CD11b, they acquired new surface proteins, such as HLA-DR and the co-stimulation molecule CD80, which are associated with antigen presentation. We note a similar instance of inflammatory Functions of long-lived neutrophilsreprogramming in synovial fluid neutrophils, a percentage of which expressed functional HLA-DR. 50 Neutrophils from patients with vasculitis and systemic bacterial infections also acquire novel surface receptors and functions, such as expression of CD64, CD14 and neoexpression of HLA-DR and CD83. 51,52 In addition, we showed that, relative to freshly isolated neutrophils, long-lived neutrophils have increased cell surface ICAM-1, neoexpression of CD49d with concomitant diminution in expression of the traditional neutrophil adhesion integrins b 1 and b 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be speculated that even though neutrophils may be less potent than DCs in processing and presenting antigenic peptides to T cells and be less relevant for the induction of primary T cell responses in the draining lymph nodes, the sheer quantity of neutrophils rapidly recruited to the site of infection will easily outnumber local DCs that are relatively sparse in peripheral tissues. Indirect evidence for the existence of APC-like neutrophils comes from studies in patients with various infectious and non-infectious inflammatory diseases [90][91][92][93][94][95][96], most notably in acute sepsis where circulating neutrophils possess a phenotype similar to Vc9/Vd2 T cell-primed neutrophils and are similarly capable of cross-presenting soluble proteins to antigen-specific CD8 + T cells [10]. These findings support the existence of an effective sentinel network comprised of Vc9/Vd2 T cells and their crosstalk with neighboring immune and non-immune cells [4], and identify a novel role for human unconventional T cells in shaping the transition of the innate to the adaptive phase of anti-microbial responses.…”
mentioning
confidence: 99%